EATING PRACTICE OF SUNDANESE WOMEN IN THE POSTPARTUM PERIOD - Ermiati E; Restuning Widiasih; Anita Setyawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Cultural practices are still very strong in Indonesia, but sometimes they are contrary to health. So that often these cultural practices cause pain and even death. Abstinence to eat in Sundanese society is a cultural practice. The purpose of this study was to determine the practice of eating in mothers of postpartum in Sundanese culture. This type of research is a quantitative descriptive. The sample in this study was 25 mothers of postpartum with criteria of Sundanese husband and wife and the mother was still in puerperium for up to 40 days. The research instrument was in the form of a questionnaire about food culture practices, the data were analyzed by the presentation. The results showed that 22 (88%) of postpartum women abstain of eating. Types of restrictions that eating eggs, fish, meat, natural water, fruits, eating soup and eating a lot. There is still abstinence from eating in the postpartum women which can cause late recovery of health in the mother of postpartum, it is expected that the health center provides counseling about the nutritional needs of mothers of postpartum and discusses each type of food that is abstinence food in the community.Keywords: Sundanese Culture, postpartum, practice.